Factors Predicting Exclusive Breastfeeding among Thai Adolescent Mothers at 6-months Postpartum - Khonsung, Panchan; Yimyam, Susanha; Xuto, Piyanut; Chaloumsuk, Nonglak (Pacific Rim International Journal of Nursing Research, 2020)
The benefits of breastfeeding to infant and maternal health are widely recognized, however, the exclusive breastfeeding rate in Thailand remains low, especially among adolescent mothers. To better understand this, we investigated the relationships and predictability of selected factors on breastfeeding among Thai adolescent mothers during 6-months postpartum in a cross-sectional predictive. One hundred and ninety-five adolescent mothers were purposively selected from six hospitals in the north of the country. In addition to collecting demographic data we used six self-administered instruments: The Pregnancy Intention and Breastfeeding Practice Questionnaire; the Perceived Benefits of Breastfeeding Questionnaire; the Perceived Barriers to Breastfeeding Questionnaire; the Breastfeeding Self-Efficacy Short-Form Scale, the Maternity Care Practice Questionnaire, and the Family Support Questionnaire. Data were analyzed using descriptive statistics, Fisher’s exact test and multivariate logistic regression. Findings indicated that the only predictor of exclusive breastfeeding was breastfeeding self-efficacy. Strategies to increase breastfeeding self-efficacy in Thai adolescent mothers should be further researched and developed for midwifery practice.